Metabolic engineering of Halomonas elongata: Ectoine secretion is increased by demand and supply driven approaches - Hobmeier, Karina; Oppermann, Martin; Stasinski, Natalie; Kremling, Andreas; Pflüger-Grau, Katharina; Kunte, Hans Jörg; Marin-Sanguino, Alberto (Frontiers in Microbiology, 2022)
The application of naturally-derived biomolecules in everyday products, replacing conventional synthetic manufacturing, is an ever-increasing market. An example of this is the compatible solute ectoine, which is contained in a plethora of treatment formulations for medicinal products and cosmetics. As of today, ectoine is produced in a scale of tons each year by the natural producer Halomonas elongata. Bioprocesses face a strong pressure for optimization due to their need to compete with chemical synthesis from cheap sources such as petrochemicals. In this work, we explore two complementary approaches to obtain genetically improved producer strains for ectoine production. On one hand, we explore the effect of increased precursor supply (oxaloacetate) on ectoine production and on the other hand we implemented an increase on ectoine demand on the pathway through the overexpression of a transporter. The supply driven approach led to 45% increased ectoine titers in two different strains. This increase was attributed to the removal of phosphoenolpyruvate carboxykinase PEPCK, which allowed the conversion of 17.9% of the glucose substrate to ectoine. For the demand driven approach, we investigated the potential of the TeaBC transmembrane proteins from the ectoine-specific TRAP transporter as export channels to improve ectoine excretion. In the absence of the substrate-binding protein TeaA, an overexpression of both subunits TeaBC facilitated a three-fold increased excretion rate of ectoine. Individually, the large subunit TeaC showed an approximately five times higher extracellular ectoine concentration per dry weight compared to TeaBC shortly after its expression was induced. By using either strategy, the ectoine synthesis and excretion in H. elongata could be boosted drastically. The inherent complementary nature of these approaches point at a coordinated implementation of both as a promising strategy for future projects in Metabolic Engineering. Moreover, a wide variation of intracelllular ectoine levels was observed between the strains, which points at a major disruption of mechanisms responsible for ectoine regulation in strain KB2.13.